Distribution of the Product of k Maxima from Uniform Ordered Samples - Al-Abood, Akram Mohammed (Al-Nahrain Journal of Science, 2011)
In this paper, we consider the distribution formulation of the productofk maxima of independent uniformly distributed samples over the interval (0,1), where the random variables of the k samples are arranged individually in ascending order of magnitude. Farthermore the distribution moments about origin are constructed.